PERBANDINGAN SAHAM BERBASIS SYARIAH DENGAN SAHAM KONVENSIONAL SEBAGAI ANALISA KELAYAKAN INVESTASI BAGI INVESTOR MUSLIM - muthoharoh muthoharoh; Sutapa Sutapa (Jurnal Akuntansi Indonesia, 2014)
The phenomenon of the lack of confidence Indonesian investors to invest more effort to control the country’s wealth as his own one of them due to lack of knowledge . Including for Indonesian Muslim businessmen , is an alternative investment of choice muamalah . But in this investment activity , there are still concerns the Muslimsagainst the perception of potential investors speculation or gharar . Therefore, the Indonesia Stock Exchange ( IDX ) follow up these concerns by launching Islamic products including Islamic stocks are grouped in two Islamic Indices , Jakarta Islamic Index ( JII ) in 2000 and Indonesia Sharia Stock Index ( ISSI ) in 2011 . The purpose of this study is to analyze and provide empirical evidence that the rate of return and risk performance of Islamic stocks better than conventional stocks . The population is all listed companies that issued shares listed on the Indonesia Sharia Stock Index ( ISSI ) for a group of Islamic stocks and Stock Price Index (CSPI ) for conventional stock group . The sampling method used was purposive sampling method in order to obtain 207 samples . Analytical techniques used include : the classical assumption of normality , descriptive statistical tests , and hypothesis testing are processed using SPSS software version 16 . The results showed that there are significant differences in the performance of stocks in which the conventional stock sharia Islamic stocks have performed much better than the conventional stock .